1999
DOI: 10.1016/s1161-0301(99)00012-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects on nutrients and on grain quality in spring wheat crops grown under elevated CO2 concentrations and stress conditions in the European, multiple-site experiment ‘ESPACE-wheat’

Abstract: Nutrient element concentrations and grain quality were assessed in spring wheat grown under elevated CO 2 concentrations and contrasting levels of tropospheric ozone at different nitrogen supply rates at several European sites. Carbon dioxide enrichment proved to affect nutrient concentrations in a complex manner. In green leaves, all elements (with exception of phosphorus and iron) decreased. In contrast, effects on the element composition of grains were restricted to reductions in nitrogen, calcium, sulphur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(78 citation statements)
references
References 43 publications
(20 reference statements)
5
71
2
Order By: Relevance
“…It suggests that the cumulative effects of E-O 3 on plant N metabolism might be much complicated in some key processes, e.g. the N pool size stored in vegetative tissues, which appears to determine the amount of available N during seed filling [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It suggests that the cumulative effects of E-O 3 on plant N metabolism might be much complicated in some key processes, e.g. the N pool size stored in vegetative tissues, which appears to determine the amount of available N during seed filling [17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the variation of leaf N status over time is essential to understand the underlying mechanism in crop yield loss and photosynthetic processes after exposure to elevated O 3 . Existing results demonstrated that elevated O 3 increased foliar N level in fen species [14], significantly decreased nitrate reductase activity in rice leaves [15], but had no significant effects on nutrient element concentrations in different tissues in wheat [16,17]. For soybean, the negative effects of O 3 on primary carbon metabolism have been well investigated, as indicated by stimulated aging and senescence, decreased photosynthesis and leaf chlorophyll content, impeded electron transport in the light reaction before senescence [18,19], a shorter development stage for carbon fixation [20] and relatively longer time for stomatal closure [21].…”
Section: Introductionmentioning
confidence: 93%
“…The impacts of changes in CO 2 concentrations on micronutrients, especially those implicated in "hidden hunger" [42], in food plants also need to be considered. Trends are emerging that decreases in micronutrients such as iron and zinc may occur in the grains of rice and wheat in response to elevated CO 2 , although this is not always the case [204][205][206][207]. Again, these issues have received relatively little attention (compared to yields) in the context of the nutritional aspects of achieving food security.…”
Section: Cassava Production In a High Co 2 Worldmentioning
confidence: 99%
“…In wheat the reduced contents of protein in the grains, including gluten, decreased the quality of the flour and hence, the volume of bread loaves as a result of exposure to high CO 2 concentration in chambers 10 and in FACE treatments. 11 Rice grains produced under elevated CO 2 in chambers exhibited lower mineral and protein contents, while amylose content was higher than in those grown under ambient CO 2 .…”
Section: Introductionmentioning
confidence: 99%